2002
DOI: 10.1046/j.1439-0523.2002.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tools for clone identification: the case of the grapevine cultivar ‘Traminer’

Abstract: In viticulture, biotype identification problems have traditionally been solved using ampelography, ampelometry and chemical traits analysis. However, these tools have resulted in several false attributions, in particular when used at the clonal level. The availability of relatively cheap, reliable and reproducible tools to identify genetic differences at the clonal level would greatly facilitate the work of clonal patenting. In this work, 24 accessions of ‘Traminer’ cultivars were characterized using molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 23 publications
6
71
1
Order By: Relevance
“…Kozjak et al (2003) tested some selected accessions from the collection vineyard in Komen with 6 microsatellite loci, also known as simple sequence repeats (SSR), and found that two Refošk samples are probably different from cultivar Refošk, showed different patterns, while other accessions revealed identical SSR allelic profiles. The insufficient clone discrimination ability of SSR molecular markers was also stated in other papers (Imazio et al, 2002;Laucou et al, 2011), although microsatellite markers have been widely used for grapevine cultivar identification, defining synonyms and homonyms, and for pedigree reconstruction (Cipriani et al, 2010;Laucou et al, 2011;Rusjan et al, 2012). Molecular markers that have been used on grapevine in several studies to detect intravarietal variability are the inter simple sequence repeats (ISSR) (Regner et al, 2000), amplified fragment length polymorphism (AFLP) (Cervera et al, 1998;Fanizza et al, 2003;Imazio et al, 2002;Konradi et al, 2007;Meneghetti et al, 2012), selective amplification of microsatellite polymorphic loci (SAMPL) (Cretazzo et al, 2010;Meneghetti et al, 2012), microsatellite amplified fragment length polymorphism (M-AFLP) (Cretazzo et al, 2010;Meneghetti et al, 2012) and specific sequence amplified polymorphism (S-SAP) (Carrier et al, 2012;Stajner et al, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…Kozjak et al (2003) tested some selected accessions from the collection vineyard in Komen with 6 microsatellite loci, also known as simple sequence repeats (SSR), and found that two Refošk samples are probably different from cultivar Refošk, showed different patterns, while other accessions revealed identical SSR allelic profiles. The insufficient clone discrimination ability of SSR molecular markers was also stated in other papers (Imazio et al, 2002;Laucou et al, 2011), although microsatellite markers have been widely used for grapevine cultivar identification, defining synonyms and homonyms, and for pedigree reconstruction (Cipriani et al, 2010;Laucou et al, 2011;Rusjan et al, 2012). Molecular markers that have been used on grapevine in several studies to detect intravarietal variability are the inter simple sequence repeats (ISSR) (Regner et al, 2000), amplified fragment length polymorphism (AFLP) (Cervera et al, 1998;Fanizza et al, 2003;Imazio et al, 2002;Konradi et al, 2007;Meneghetti et al, 2012), selective amplification of microsatellite polymorphic loci (SAMPL) (Cretazzo et al, 2010;Meneghetti et al, 2012), microsatellite amplified fragment length polymorphism (M-AFLP) (Cretazzo et al, 2010;Meneghetti et al, 2012) and specific sequence amplified polymorphism (S-SAP) (Carrier et al, 2012;Stajner et al, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…However, in order to display the capacity of AFLP markers and to recommend a minimum primer number for genetic analysis in rootstock discrimination, similarity ratios of single-and double-combination primers were determined. While Cervera et al (1998) defined the genotypes showing similarity higher than 0.900 as identical, Imazio et al (2002) identified 0.910 similarity between two different varieties, Pinot noir and Elbing. Also, Fossati et al (2001) found 0.920 similarity between two different varieties, Rossera and Urban.…”
Section: Distinctive Capacity Of the Aflp Markers For Rootstock Genotmentioning
confidence: 99%
“…Although the molecular method AFLP has been successfully used for the identification and discrimination of grapevine cultivars and the determination of the degree of genetic similarity between varieties, clones and rootstocks (Vignani et al, 2002;Imazio et al, 2002;Fanizza et al, 2005;Blaich et al, 2007;Stenkamp et al, 2009;Alba et al, 2011;Anhalt et al, 2011;Meneghetti et al, 2012;Shinde et al, 2013), the combined use of the ampelographic description for the selection of the proper sample, especially in the case of heterogeneous groups of grapevine varieties, as is the 'Mavroudia' group, is deemed necessary.…”
Section: Introductionmentioning
confidence: 99%